BIOGRAFI SUWARDI MS SEBAGAI TOKOH SEJARAWAN DAN BUDAYAWAN MELAYU RIAU - Reza Wydia Anggriani Wydia Anggriani; Isjoni Ishaq Isjoni Ishaq; Marwoto Saiman Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Biography is a story of a person’s life history comes from a true story. Biography tells of a process starting from childhood of the characters including family background and environtment, the emergence of ideals in the mind of the leaders to engage in his favorite field. The authors raise a biography about the life journey of a person who really loves the history and culture of the malay, devoted himself to studying it. Not many figures who are devoted to the history and culture of the malay world. Among them there Suwardi MS name a Historian and Cultural. Suwardi MS name already known in Riau, in the world of Malay culture and local History. The purpose of this study was to determine the life history Suwardi MS as Historians and Culture figures wither Riau, to determine the role of Suwardi MS as Historians and Culture figures wither Riau, to determine the obstacles and how to overcome them by Suwardi MS, to know Suwardi MS as Historians and Cultural figures wither Riau. The method used is the method of historical and documentary in which the data were collected through interviews, documentation, and library Studies. Analysis of data using qualitative techniques of writing. When the study began filing title until the completion of a revised proposal last essay writer. The results showed in the biography Suwardi MS as historians and cultural Riau of the Malay, Suwardi has conducted various activities such as, pioneered the publishing media, national and international seminars, as well as conducting research history. Based on these results it can be concluded Suwardi MS has an important role in developing cultural values as well as the local historian in Riau.Keywords: Biography, Historian, Cultural, Riau